Facile synthesis of highly active fluorinated ultrathin graphitic carbon nitride for photocatalytic H2 evolution using a novel NaF etching strategy. Issue 48 (30th July 2018) - Liu, Yanfei; Wang, Junjie; Yin, Chaochuang; Duan, Huazhen; Kang, Shifei; Cui, Lifeng
Abstract : Although graphitic carbon nitride (GCN) has been intensively studied in photocatalytic research, its performance is still hindered by its inherently low photo-absorption and inefficient charge separation. Abstract : Although graphitic carbon nitride (GCN) has been intensively studied in photocatalytic research, its performance is still hindered by its inherently low photo-absorption and inefficient charge separation. Herein, we report a simple NaF solution treating method to produce fluorinated and alkaline metal intercalated ultrathin GCN with abundant in-plane pores and exposed active edges, and therefore an enhanced number of actives sites. Compared to bulk GCN, NaF treated GCN has a larger specific surface area of 81.2 m 2 g −1 and a relatively narrow band gap of 2.60 eV, which enables a 6-fold higher photocatalytic rate of hydrogen evolution.